2020
DOI: 10.1093/biomethods/bpaa017
|View full text |Cite
|
Sign up to set email alerts
|

Easing diagnosis and pushing the detection limits of SARS-CoV-2

Abstract: Rigorous testing is the way forward to fight the COVID-19 pandemic. Here we show that the currently used and most reliable RT-PCR based SARS-CoV-2 procedure can be further simplified to make it faster, safer, and economical by eliminating the RNA isolation step. The modified method is not only fast and convenient but also at par with the traditional method in terms of accuracy, and therefore, can be used for mass screening. Our method takes about half the time and is cheaper by about 40% compared to the curren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 12 publications
0
30
2
Order By: Relevance
“…RT-PCR being laborious, time-consuming, requiring high-end equipment and trained manpower, it’s been of limited use in the resource-constrained settings. However, a recent study has shown the use of direct swab sample which will further simplify the test by eliminating the RNA isolation step ( Kiran et al, 2020 ).…”
Section: Covid-19 Diagnosticsmentioning
confidence: 99%
“…RT-PCR being laborious, time-consuming, requiring high-end equipment and trained manpower, it’s been of limited use in the resource-constrained settings. However, a recent study has shown the use of direct swab sample which will further simplify the test by eliminating the RNA isolation step ( Kiran et al, 2020 ).…”
Section: Covid-19 Diagnosticsmentioning
confidence: 99%
“…Recently, RNA extraction from the swab samples was shown to be dispensable thereby enabling direct processing of the samples for qRT-PCR in COVID-19 screening [14] as well as in other respiratory viral infections [23, 24]. Collecting the samples in dry-swab form has been demonstrated to be effective in preserving the viral content and also much more bio-safe [23, 24].…”
Section: Resultsmentioning
confidence: 99%
“…The supernatants were titrated for infectious particle count by plaque-forming assay. In the case of dry-swab sample, the swab was first soaked in TE buffer for 30 minutes [14] and further stored at −80°C freezers. Later the sample was used as inoculum for infection similar to VTM.…”
Section: Methodsmentioning
confidence: 99%
“…(a) One-step PCR: CSIR-CCMB has developed a one-step RTqPCR reaction with dry swab samples (Figure 1) [17]. The testing centres can send samples without VTM, and thus, the safety and cost of packing and unpacking samples at the sample collection and testing centres can be improved.…”
Section: Optimisation Of Testing Proceduresmentioning
confidence: 99%